2012
DOI: 10.1039/c1an15897j
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanosensors for highly sensitive and selective detection of bacillus Calmette-Guérin

Abstract: With current concerns of the global threat from tuberculosis, it has become important to rapidly identify the bacteria. Traditional technologies involving isolation and amplification of the pathogenic bacteria are complicated and time-consuming. In this work, we describe a sensitive NMR-based detection method to identify bacteria via bacteria-induced self-assembly of magnetic nanoparticles. Bacillus Calmette-Guérin (BCG) was used as a surrogate for Mycobacterium tuberculosis. We prepared the probes by covalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Recent decades have shown that the use of nanoscale preparations allows for highly sensitive detection of various chemicals and bioligands (e.g., peptides, proteins, antibodies, viral particles, antibiotics, mRNA, etc.) in biological fluids in real time [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. MPs were synthesized through the chemical coprecipitation of ferrous (Fe 2+ ) and ferric (Fe 3+ ) chloride and coated with a 10 kDa dextran via the cross-link with epicholorohydrin.…”
Section: Discussionmentioning
confidence: 99%
“…Recent decades have shown that the use of nanoscale preparations allows for highly sensitive detection of various chemicals and bioligands (e.g., peptides, proteins, antibodies, viral particles, antibiotics, mRNA, etc.) in biological fluids in real time [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. MPs were synthesized through the chemical coprecipitation of ferrous (Fe 2+ ) and ferric (Fe 3+ ) chloride and coated with a 10 kDa dextran via the cross-link with epicholorohydrin.…”
Section: Discussionmentioning
confidence: 99%
“…To meet this challenge, a sensitive NMR-based detection method to identify bacteria via bacteria-induced selfassembly of MNPs was developed by Liang et al [73]. With a detection limit of as few as 8 bacteria cells per mL in experimental samples within 1 h, the method showed great potential for rapid detection of M. tuberculosis in clinical samples.…”
Section: Nuclear Magnetic Resonance (Nmr) Sensormentioning
confidence: 99%
“…Recently, magnetic relaxation switching (MRS) sensors that depend on target-induced aggregation (or disaggregation) of superparamagnetic nanoparticles (SMNs) are employed to quantify a wide range of targets. [9][10][11] In a typical MRS sensor, the target can induce a change in the state of the SMNs (from dispersed to aggregated) via specic donor-receptor recognition, and this state change of the SMNs induces a heterogeneous magnetic eld, which affects the transverse relaxation time (T 2 ) of surrounding water molecules. The DT 2 value (the change of T 2 ) is related to the degree of aggregation of the SMNs, and this degree of aggregation is dependent on the amount of target in the sample; thus, DT 2 can be employed as a signal readout.…”
mentioning
confidence: 99%